Manajemen Redaksi Komunikasi Nusantaratv.com dalam Membangun Reputasi di Era Persaingan Industri Media Online - Deni Candra; Iqbal Shamiago; Roi Rohmansah; Wiji Setiawan (STIKes Ibnu Sina Ajibarang, 2024)
Nusantaratv.com, an online news portal founded in 2020, has succeeded in building a reputation as a trusted source of information in the digital era. This research aims to understand how Nusantaratv.com's editorial management contributes to building a positive reputation. This research uses the POAC (Planning, Organizing, Actuating, and Controlling) model in analyzing various relevant aspects. Using the POAC Model as a comprehensive approach to management which includes planning, organizing, implementing and controlling. This research uses a qualitative method with data collection techniques in the form of literature study, observation, documentation and interviews. The research results show that Nusantaratv.com implements an effective editorial management strategy, including: Planning: Developing a comprehensive communication strategy to deliver quality content, with the main target audience being young viewers aged 18-35 years. Organizing: Forming a special team consisting of content writers, graphic designers, video editors and social media managers to manage communication campaigns. Implementation (Actuating): Motivating and guiding the team to carry out planned tasks, with effective internal communication and good coordination. Supervision (Controlling): Monitoring and evaluating the results of communication activities, by making adjustments if necessary to ensure communication objectives are achieved. A data-driven approach and analysis of user feedback allows Nusantaratv.com to remain relevant and meet the needs of its ever-evolving audience. Collaboration with various stakeholders also helps Nusantaratv.com expand its reach and enrich its content.